Sharing a Vision Systems and Algorithms for Collaboratively-Teleoperated Robotic Cameras - Song, Dezhen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The monograph written by Dezhen Song is focused on a robotic camera simultaneously controlled by multiple online users via the Internet. A challenging match between the collaboratively tele-operated robotic cameras and the needs from nature environment observation is sought, which greatly extends the domain of online robots in both application and technology development directions, including building construction site monitoring, public space surveillance, and distance education. New solutions are proposed which demonstrate the enormous potential of Internet-based infrastructures for immediate success in the market.
I: Systems -- The Co-Opticon System: Interface, System Architecture, and Implementation of a Collaboratively Controlled Robotic Webcam -- The Tele-Actor System: Collaborative Teleoperation Using Networked Spatial Dynamic Voting -- II: Algorithms -- Exact Frame Selection Algorithms for Agile Satellites -- Approximate and Distributed Algorithms for a Collaboratively Controlled Robotic Webcam -- An Approximation Algorithm for the Least Overlapping p-Frame Problem with Non-Partial Coverage for Networked Robotic Cameras -- Unsupervised Scoring for Scalable Internet-Based Collaborative Teleoperation -- III: Deployment -- Projection Invariants for Pan-Tilt-Zoom Robotic Cameras -- Calibration Algorithms for Panorama-Based Camera Control -- On-Demand Sharing of a High-Resolution Panorama Video from Networked Robotic Cameras -- Conclusions and Future Work.
Keywords: Engineering; Artificial intelligence; Image processing; Quantum optics; Control engineering; Robotics; Mechatronics; Automation; Electrical engineering; Engineering; Robotics and Automation; Communications Engineering, Networks; Image Processing and Computer Vision; Control, Robotics, Mechatronics; Quantum Optics; Artificial Intelligence (incl. Robotics).; Electronic books